Effect of Work Experience and Work Facilities on Employee Performance with Work Motivation as an Intervening Variable Binjai City Department of Transportation - Pranata Ginting, Ryanda; Isa Indrawan, Muhammad (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
The purpose of this study was to analyze the effect of work experience and work facilities on employee performance with work motivation as an intervening variable. The type of research used is associative quantitative. The research location was at the Binjai City Transportation Service Office. The study population was 79 employees. The sample used was 79 employees (saturated sample). The data source used is the primary data source. The research model used is path analysis with the Smart PLS measurement tool. The result of the research is that work facilities have a positive and significant effect on employee performance. Work facilities have a positive and significant effect on work motivation. Work motivation has a positive and insignificant effect on employee performance. Work experience has a positive and significant effect on employee performance. Work experience has a positive and significant effect on work motivation. Work facilities have no significant positive effect on employee performance through work motivation. Work Experience Work has no significant positive effect on Employee Performance through Work Motivation.